Coefficient Estimates for Some Classes of Biunivalent Function Associated with Jackson q-Difference Operator - Ekram E. Ali; Abdel Moneim Lashin; Abeer M. Albalahi (Journal of Function Spaces)
Using the Jackson q-difference operator, we present two new subclasses of biunivalent functions. Furthermore, we estimate the initial Taylor-Maclaurin coefficients a2 and a3 of functions belonging to these new subclasses. Our results generalize some of the previously related works of several authors.